Implant survival rate of patients in Dental Hospital Hasanuddin University: 8 years evaluation - Bahruddin Thalib; Rifaat Nurrahma; Asmawati; Nurlindah Hamrun; Alqarama Mahardika; Ian Afifah Sudarman; Rezky Wahyuni Syamsuddin (Indonesian Journal of Prosthodontic, 2022)
Data on dental implant treatment's success and survival rate are still limited. Meanwhile, the data on the success and survival after implant placement and restoration can be used to evaluate materials, improve the dental implant treatment, and enhance the service quality at Hasanuddin University Dental Hospital. The purpose of this study is to analyze the dental implant survival rate, the contributing factors that enhance the survival rate, and the factors causing the failure of the dental implants at the Prosthodontic Clinic of Dental and Oral Hospital, Hasanuddin Uni-versity. The final study group consisted of 11 patients with 20 implants. Implant failure was categorized based on implant loss, mobility, or removal due to severe peri-implant infection or implant fracture. Implant survival rates were grouped based on sex, age, smoking habit, placement location, diameter, length, and placement time. The value of implant survival rate was assessed based on the presentation of successful implants. Of all 20 cases, five implants failed, indicating a cumulative implant survival rate of 75%. Based on the failure period, there are initial failure cases before loading and late failure cases after loading. One implant failed within the first six months, and two implants failed 2 years after insertion of the superstructure. The leading cause of implant failure before loading is osseointe-gration failure. In the case of implants that failed after installing the superstructure, peri-implantitis occurs continous-ly. It was concluded that the implant survival rate for patients at the Hasanuddin University Dental Hospital is 75%. Dental implant survival rates include gender, age, implant placement location, smoking habits, implant diameter, length, and immediate or delayed implant placement. The factors causing the failure of the implant in this study were osseointegration failure and peri-implantitis